Development of the Russian Economy’s Agricultural Sector Under the Conditions of Food Sanctions (2015-2016) - KOPTSEVA, Natalia P.; KIRKO, Vladimir I. (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).13, 2017)
The Russian economy is in crisis. In 2014, the Russian government has introduced a food sanctions. This caused a certain economic processes in agriculture, post-Soviet Russia. Now the problem of food security of Russia practically solved. The main figures of the Russian agrarian economy are large agricultural holdings. The value of small farms is reduced. However, the agrarian economy of post-Soviet Russia is on the verge of a new economic crisis associated with the termination of public investment. We discuss a new strategy to overcome the agrarian crisis in modern Russian economy. The most promising strategy is an increase in food imports in Asia and Africa. A food import to the EU is not possible, since the EU has great demands on the quality and safety of food imports.